Disseminated Coccidioidomycosis With Orbital Osteomyelitis and Periorbital Abscess. Issue 5 (September 2021) - Reed, Donovan S.; Kostosky, Nicole; Epstein, Aliza; Blaydon, Sean; Durairaj, Vikram; Somogyi, Marie
Abstract : Coccidioidomycosis osteomyelitis involving the orbital bones is exceedingly rare and is often misdiagnosed initially as other inflammatory or infectious conditions. No clear guidelines currently exist regarding appropriate management. The authors present an atypical presentation of disseminated coccidioidomycosis in an immunocompetent child with frontal bone superotemporal orbital rim osteomyelitis and associated periorbital abscess, successfully managed with surgical debridement through an upper eyelid crease incision. Abstract : Presented is a case of disseminated coccidioidomycosis in a child with frontal bone superotemporal orbital rim osteomyelitis and associated periorbital abscess, successfully managed with surgical debridement and abscess drainage through an upper eyelid crease incision.